(untitled) (Update Dental College Journal, 2013)
Obturator prostheses are considered to be the preferred choice for the restoration of maxillary defects. Patients with palatal insufficiency, speech and deglutition becomes impaired, thereby requiring prosthodontic rehabilitation. The prosthodontic rehabilitation of patients with acquired defects of the maxilla after surgical resection is the complete responsibility of a maxillofacial prosthodontist. He has to recreate an artificial barrier between the cavities and thus restore the functional capabilities of speech, mastication and swallowing. Palatal obturator is the only substitute which covers the defect and contributes to normal speech production. It eliminates hypernasality and improves the communication. DOI: http://dx.doi.org/10.3329/updcj.v1i2.13983 Update Dent. Coll. j. 2011: 1(2): 25-28